2015
DOI: 10.1073/pnas.1501759112
|View full text |Cite
|
Sign up to set email alerts
|

PDGFB-based stem cell gene therapy increases bone strength in the mouse

Abstract: Substantial advances have been made in the past two decades in the management of osteoporosis. However, none of the current medications can eliminate the risk of fracture and rejuvenate the skeleton. To this end, we recently reported that transplantation of hematopoietic stem/progenitor cells (HSCs) or Sca1 + cells engineered to overexpress FGF2 results in a significant increase in lamellar bone matrix formation at the endosteum; but this increase was attended by the development of secondary hyperparathyroidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 40 publications
5
69
0
Order By: Relevance
“…Femurs with fractures and intact femurs were harvested at day 28, fixed in 4% paraformaldehyde, and subjected to μCT analysis using a Scanco vivaCT μCT system with a voxel size of 10.5 μm. Mineralized callus bone was determined as previously described (49). Each sample was contoured around the periosteal circumference to determine the volume of interest (VOI) at a fracture site.…”
Section: Methodsmentioning
confidence: 99%
“…Femurs with fractures and intact femurs were harvested at day 28, fixed in 4% paraformaldehyde, and subjected to μCT analysis using a Scanco vivaCT μCT system with a voxel size of 10.5 μm. Mineralized callus bone was determined as previously described (49). Each sample was contoured around the periosteal circumference to determine the volume of interest (VOI) at a fracture site.…”
Section: Methodsmentioning
confidence: 99%
“…35,[46][47][48] Among the abnormalities during the development, resembling defects in dendritic spine density, impairment in hippocampus-dependent memory formation, and long-term potentiation are caused by deletion of either PDGFRβ or EphA4, suggesting neuron development and maturation require the presence of both PDGFRβ and EphA4. 21,49,50 These findings suggest that the PDGFRβ/EphA4 receptor complex mediates a variety of signals.…”
mentioning
confidence: 94%
“…A slight reduction of PDGF-BB expression was also found in the MSCs-IL-4-PDGF group compared to the MSCs-PDGF group in both BALB/c and C57BL/6 MSCs (Fig. 1C, D), but levels in both strains were also in the therapeutically effective range of expression [8].…”
Section: Resultsmentioning
confidence: 75%
“…Platelet-derived growth factor (PDGF)-BB stimulates MSCs, resulting in enhanced angiogenesis and osteogenesis in a dose-dependent manner [6,7]. Osteogenesis was enhanced by relatively low doses of PDGF-BB in vitro; in vivo studies showed that trabecular bone formation and trabecular connectivity were increased by overexpression by lentiviral vector of PFGF-BB under a relatively week PGK promoter, completely avoiding osteomalacia and secondary hyperparathyroidism seen with higher doses [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation